The Effectiveness of the Use of Cell Dump Data Techniques by the Reskrim Sat to Help the Process of Investigation of the Crime of Curanmor in the Jurisdiction of the Surabaya Polrestabes (Advances in Police Science Research Journal, 2024)
This research is motivated by the very frequent phenomenon of theft in the jurisdiction of the Surabaya Police. In this case, it resulted in a lot of loss of both property and lives. The Surabaya Police Criminal Investigation Unit carries out the handling process using the cell dump technique. Therefore, in an effort to create a conducive social security and security situation, it is necessary to handle theft cases using the cell dump data technique carried out by the Surabaya Police Criminal Investigation Unit. This research uses the concept of effectiveness, the concept of use, the concept of the cell dump technique, the concept of the Criminal Investigation Unit, the concept of investigation, the concept of criminal acts of theft. Meanwhile, the theories used are systems analysis theory from a scientific perspective and management theory. The approach in this research is a qualitative approach with descriptive research type. The data sources used are primary data and secondary data. The informants in this research were the Surabaya Police Chief, Criminal Investigation Unit Head, Head of Jatanras Unit, and the analysis team. Data collection techniques in this research are interview techniques, observation techniques, and literature study. And the data analysis techniques used are data reduction, data presentation, and drawing conclusions. Based on the research findings and analysis carried out, the results obtained were that investigative activities were still lacking and not optimal. Therefore, it requires support from management elements so that the investigation process using the cell dump data technique can run effectively. The discussion so that the author can conclude that the process of investigating the theft case was carried out using the cell dump data technique. The effectiveness of using the cell dump data technique to assist the process of investigating criminal acts of theft at the Surabaya Police can be effective through optimizing management elements. The first suggestion is to propose to the analysis team to use the latest application. Second, there is a need to increase human resources with training in the use of technology.
Keywords: Effectiveness, Cell dump, Crime